Improving English Speaking Skills Through English Speaking Club For Teenagers Of Budi Mulya Village, Banyuasin Regency - Dewi Warna (CV. Doki Course and Training, 2025)
This community service aims at improving English speaking skills through an English Speaking Club for teenagers of Budi Mulya Village, Banyuasin Regency. The location of the English Speaking Club is Budi Mulya Village, Air Kumbang District, Banyuasin Regency. The target of this activity is the village youth in Budi Mulya Village, totaling 25 people. These village youth are aged between 12 to 18 years old. Before the English Speaking Club was formed, a driving team was formed to assist in the formation and implementation of Speaking English Club activities in Budi Mulya Village. The team consisted of 1 lecturer of English Education Study Program and 3 students of English Education Study Program, Faculty of Tarbiyah and Keguruan Sciences, UIN Raden Fatah Palembang, who carried out the Real Work Lecture for 40 days (14 January to 24 February 2025) in Budi Mulya Village, Banyuasin Regency, and 1 English teacher of SDN 15 Air Kumbang. The result of this community service covered some steps, including (1) the process of socialization and recruitment of members; (2). determining the schedule and learning materials; and (3) the activities carried during the community service. With the ability to communicate in English that Budi Mulya adolescents gained at English Speaking Club, they could also participate in student exchange programs, seminars, discussions, and various other activities that could broaden their horizons.